Comparison of persistent organic pollutants (POPs) between small cetaceans in coastal and estuarine waters of the northern Gulf of Mexico. (August 2019) - Balmer, Brian; Ylitalo, Gina; Watwood, Stephanie; Quigley, Brian; Bolton, Jennie; Mullin, Keith; Rosel, Patricia; Rowles, Teri; Speakman, Todd; Wilcox, Lynsey; Zolman, Eric; Schwacke, Lori
Abstract: Small cetaceans continue to be exposed to elevated levels of persistent organic pollutants (POPs). The goals of this study were to use data from remote biopsy sampling and photographic-identification to compare POP concentrations between small cetacean stocks in the northern Gulf of Mexico. During 2015–2017, 74 remote biopsies were collected in St. Andrew Bay and adjacent coastal waters from two species: common bottlenose dolphin ( Tursiops truncatus ) (N = 28, ♀; N = 42, ♂) and Atlantic spotted dolphin ( Stenella frontalis ) (N = 2, ♀; N = 2, ♂). Common bottlenose dolphin POP concentrations were significantly higher in St. Andrew Bay than coastal waters. Male St. Andrew Bay dolphins had the highest Σ DDT (dichlorodiphenyl-dichloroethane) levels measured in the southeastern U.S. (67 μg/g, 50–89 μg/g; geometric mean and 95% CI) and showed a significant negative relationship between Σ DDT and sighting distance from a St. Andrew Bay point source. Graphical abstract: Unlabelled Image Highlights: Elevated levels of persistent organic pollutants (POPs) have been identified in small cetacean species throughout the world Remote biopsy sampling and photographic-identification are useful tools to measure the range of POPs in small cetaceans Common bottlenose dolphins in St. Andrew Bay, Florida had the highest DDT levels measured in the southeastern U.S. There was a negative relationship identified for dolphins between DDT and distance from a St. Andrew Bay point source